PENGARUH IKLIM ORGANISASI DANSUPERVISIAKADEMIK KEPALA MADRASAH TERHADAPKOMPETENSI PEDAGOGIK GURU DIMADRASAH IBTIDAIYAH - Suryani, Suryani; Aunurrahman, Aunurrahman; Radiana, Usman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study was aimed to identify if  Wether the organizational climate and academic supervision of madrasah  ibtidaiyah  headmaster were influential to pedagogical competence of teachers in madrasah ibtidaiyah sub district Sungai Kakap , Kubu Raya district. This study applied quantitative approach. Samples in this study were teachers in Islamic elementary school in Sungai Kakap district as many as 139 teachers. Hypothetical examination in this study applied double regression technique. The result of analysis identified that (1) there was an influence of organizational climate of Islamic school (X1) to pedagogical competence of teachers (Y) as many as 47.9%, (2) there was an influence of madrasah ibtidaiyah  headmaster's competence (X2) to pedagogical competence of teachers (Y) as many as 32.4%, and (3) there was an influence of organizational climate (X1) and academic supervision of madrasah ibtidaiyah  headmaster (X2) to pedagogical competence of teachers as many as 51.2%.It could be concluded that better organizational climate and better academic supervision by madrasah ibtidaiyah  headmaster gave more significant influence to pedagogical competence of teachers in madrasah ibtidaiyah  in Sungai Kakap district, Kubu Raya distric. The suggestions were as follows; madrasah ibtidaiyah  headmaster must had comprehension on academic supervision competence, create harmony in the relationship with madrasah ibtidaiyah community so that a conducive climate could be realized, and implement programmed continual academic supervision in order to cope with problems faced by teachers during class activities,  Keywords: Organizational Climate , Academic Supervision, Pedagogic Competence